Implementasi Metode System Usability Scale Pada User Interface Sistem Informasi Management Intern - Hapsari, Ni Made Alisya Putri; Suputra, I Putu Gede Hendra (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
In an application, the user interface is one of the most important factors in system development, whether it is based on Android, iOS, desktop, or websites. To develop a good application, a maximum planning and design stage is needed, especially in the design of the user interface. A bad user interface will affect productivity and users in visiting developed applications. On the other hand, a good user interface design can display information clearly so that users can comfortably use the application. Good or not a user interface can be determined through the subjective judgment of the user. Therefore, in this study, an evaluation of the user interface of a website-based application is being developed, namely the Internal Management Information System. The evaluation method used in this study is the System Usability Scale or SUS where an assessment will be made by the user of the user interface that has been developed then the results of the assessment will be processed to determine the feasibility of the user interface.